2012
DOI: 10.4028/www.scientific.net/amr.482-484.2270
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of 2D Model of Diffuser for Harnessing Tidal Energy

Abstract: Diffuser augmented tidal turbines are getting enormous attention due to their immense potential to increase the generated power output. Researchers around the globe are investing considerable time and financial resources in this domain. Limited research results are available for diffuser augmented tidal turbines due to their emerging nature, large and costly research and development setup, startup cost and proprietary issues. Turbine enclosed in a diffuser is based on the principle that the generated power out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A considerable amount of literature has been published on the application of CFD analysis to predict performance of shroud for wind turbines. Mehmood et al has concluded that CFD is a viable tool for diffuser shape evaluation during the early stages of turbine shroud design [6]. Abe et al has also reported that computational analysis is very useful in detailed investigation of flow fields around flanged diffusers [7].…”
Section: Design Considerations For Shroud Using Cfdmentioning
confidence: 99%
“…A considerable amount of literature has been published on the application of CFD analysis to predict performance of shroud for wind turbines. Mehmood et al has concluded that CFD is a viable tool for diffuser shape evaluation during the early stages of turbine shroud design [6]. Abe et al has also reported that computational analysis is very useful in detailed investigation of flow fields around flanged diffusers [7].…”
Section: Design Considerations For Shroud Using Cfdmentioning
confidence: 99%
“…Thus, increase mass flow rate and power output. The diffuser augmented tidal turbine generates same power with a smaller turbine diameter compared to naked turbine [3]. Consequently, diffuser augmented tidal turbine is more viable economically compared to naked turbine.…”
Section: Introductionmentioning
confidence: 99%